Methylation-Mediated Silencing of MicroRNA-497 Promotes Breast Cancer Progression Through Up-Regulation of Mucin1 - Tao, Shuang; Li, Hong; Ma, Xiuzhen; Lian, Bin; He, Jiale; Gao, Yali; Li, Jinping (Frontiers in Oncology, 2020)
Background: Potential anti-tumor effects of microRNA-497 (miR-497) have been highlighted in various malignancies including breast cancer. However, little is known about the function of miR-497 and its putative target mucin1 (MUC1) in breast cancer. The present study explored how miR-497 regulates breast cancer progression in a MUC1-dependent manner. Methods: Expression of miR-497 and MUC1 was determined in breast cancer tissues and cells. Methylation specific PCR was used to measure the methylation status of CpG islands of miR-497 promoter, while chromatin immunoprecipitation assay was used to detect recruitment of methyltransferase to the promoter region of miR-497. Alteration in expression of miR-497 (overexpression) and MUC1 (up- and down-regulation) was performed to examine their roles in breast cancer biology in vitro and in vivo. The binding affinity between miR-497 and MUC1 was investigated through a bioinformatics database and dual luciferase reporter gene assay. Results: MiR-497 was down-regulated and MUC1 was up-regulated in breast cancer tissues and cell lines. Besides, methylation induced a down-regulation of miR-497 in breast cancer. The bioinformatics analysis and dual luciferase reporter gene assay indicated that miR-497 targeted MUC1. Overexpression of miR-497 inhibited breast cancer cell proliferation and invasion and promoted the apoptosis of breast cancer cells by down-regulating MUC1. The inhibitory action of miR-497 on tumor growth was validated in vivo. Conclusion: In conclusion, miR-497 down-regulated MUC1 expression and subsequently suppressed breast cancer progression, highlighting miR-497 to be a potential biomarker and therapeutic target for breast cancer therapy.